(3GdCRgGQ GdUGajI aj TQM GdebOeI GdcGajIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s; (3GHf GdMGLH , LeGd GdOjf CHh YeQh GHf GdMGLH, LeGd GdOjf CHh YeQh GHf GdMGLH,J (B646 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdMcje GdPi CfWb GdCdSfI HLhGgQ Gdcde GddZhjI s
(3BNQgG (B:s
(3GdeSCdI GdQGHYI , bhd YHO Gddg Hf GdMQ(B: (3eJi JCJfG Jdee HfG ai OjGQfG JLO MWHG LRdkG hfGQkG JCLLkG s
(3GdfSNI ebGHdI Ydi fSNI efbhdg ef fSNI HNW GdeUfas
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B265s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs